Modern theories and practices for cyber ethics and security compliance - Yaokumah, Winfred (A volume in the advances in information security, privacy, and ethics (AISPE) book series, 2020)
"This book examines concepts, models, issues, challenges, innovations, and mitigation strategies needed to improve cyber security, cyber safety, and cyber ethics"--